Reverberation Mapping of High-Luminosity Quasars - Kaspi, Shai; Brandt, William N.; Maoz, Dan; Netzer, Hagai; Schneider, Donald P.; Shemmer, Ohad (Frontiers in Astronomy and Space Sciences, 2017)
Over the past three decades reverberation mapping (RM) has been applied to about 100 AGNs. Their broad line region (BLR) sizes were measured and yielded mass estimates of the black holes in their center. However, very few attempts were carried out for high-luminosity quasars, at luminosities higher than 1046 erg/sec in the optical. Most of these attempts failed since RM of such quasars is difficult due to a number of reasons, mostly due to the long time needed to monitor these objects. During the past two decades we carried out a RM campaign on six high-luminosity quasars. This contribution presents some of the final light curves of that RM campaign in which we measured the BLR size in C iv of three of the objects (S5 0836+71, SBS 1116+603, and SBS 1425+606). We present the C iv BLR size and luminosity relation over eight orders of magnitude in luminosity, pushing the luminosity limit to its highest point so far.